2013
DOI: 10.1016/j.vaccine.2013.03.065
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of vaccine-induced antibody responses: Impact of new technologies

Abstract: Host response to vaccination has historically been evaluated based on a change in antibody titer that compares the post-vaccination titer to the pre-vaccination titer. A four-fold or greater increase in antigen-specific antibody has been interpreted to indicate an increase in antibody production in response to vaccination. New technologies, such as the bead-based assays, provide investigators and clinicians with precise antibody levels (reported as concentration per mL) in ranges below and above those previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 17 publications
5
19
0
Order By: Relevance
“…7,8,12,23 Especially for pre-vaccination HAI titers, several authors have noted that pre-existing titers significantly affect response to vaccines. 30 In the current study, we have shown that higher pre-vaccination titers are significantly associated with higher post-vaccination titers (tables 4,5). In contrast, Sasaki et al have shown an inverse relationship between status of previous vaccination and/or higher baseline antibody level with lower immune responses.…”
Section: Discussionsupporting
confidence: 55%
“…7,8,12,23 Especially for pre-vaccination HAI titers, several authors have noted that pre-existing titers significantly affect response to vaccines. 30 In the current study, we have shown that higher pre-vaccination titers are significantly associated with higher post-vaccination titers (tables 4,5). In contrast, Sasaki et al have shown an inverse relationship between status of previous vaccination and/or higher baseline antibody level with lower immune responses.…”
Section: Discussionsupporting
confidence: 55%
“…To parse the heterogeneity of the quantitative anti-3S response, compared with immune responses against the carrier (anti-CRM197 Abs, Supplementary Fig. 1a), we performed a post-hoc analysis considering the stratification of vaccinated patients into high, low, and non-responders, previously used for the evaluation of other vaccines, 23 according to their anti-3S Ab fold-increase (≥10, >4, and ≤4, respectively) between baseline and week 48. Overall 27.8% were high responders, 22.2% low responders, and 50.0% non-responders (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Modifications could be implemented down to the atomic level to increase both immunogenicity and protective effects as has been illustrated for ST5 where a ketone was replaced by a hydroxyl group to improve stability while maintaining immunogenicity and antigenicity. One dominant criterium used to assess an adequate vaccination response in adults is a two-to fourfold change in specific antibody levels after vaccination as measured by ELISA (36,37). The semisynthetic pentavalent conjugated vaccine sPCV5 reached this standard for all serotypes except ST14 CPS.…”
Section: Discussionmentioning
confidence: 99%